AN ANALYSIS OF BUSINESS STRATEGY TO INCREASESUSTAINABLE COMPETITIVENESS IN STREET VENDORS (STUDIES IN MANG UDIN ICE BUSINESS IN BANDAR LAMPUNG) - Sapmaya Wulan; . Mahmudi (UBL, 2016)
Street Vendors is one small business that is growing rapidly in Bandar Lampung. One of them is the Mang Udin Ice business located in front of Pasar Mangga Dua Bandar Lampung.The formulation of the problems of this study are: Business strategy what can be done to increase sustainable competitiveness?The purpose of this study was to determine the business strategy of what can be done to increase sustainable competitiveness.This study used a qualitative descriptive method by using primary and secondary data; and data collection techniques by observation, interviews, documentation and questionnaires; as well as qualitative analysis method by SWOT analysis (Strengths, Weakness, Opportunities And Threats). Based on the analysis diagram Cartesian SWOT obtainedMang Udin Ice Business located in Quadrant I, business strategies can be implemented to increase sustainable competitiveness is the generic strategies are: Cost Advantage Strategy (buy raw materials in large quantities and reduce the cost of labor),Differentiation Strategy (multiply choice pruduk and increase product quality, adding a type of food products, open new business branches and do joint ventures), Focus Strategy (maintain the quality products and always maintain the cleanliness).Based on the analysis Strategic SWOT matrix, the highest scores were effective to increase sustainable competitiveness is Strength OpportunityStrategy (SO) with a score of 3.07, followed successively by Weakness Opportunity Strategy (WO) with a score of 2.57, Strength Threats Strategy(ST) with a score of 2.02 and Weakness ThreatsStrategy (WT) with a score of 1.52. Business strategy that can be performed on SO are: increase the quality of products that are superior to the competitors, increase product choice, keep clean; the WO are: increase the choice of products, open new business branches, add facilities (seating), and increase the number of workers who can be trusted; in ST are: increase the quality of products that are superior to the competitors, always maintain cleanliness and to reassess the business; and the WT are: product innovation in order to increase the variety and quality of products, as well as doing a good joint venture with the owners of capital or other business.